Adolescents learning with exhibits and explainers: the case of Maloka. Issue 3 (3rd July 2019) - Massarani, Luisa; Poenaru, Lara Mucci; Norberto Rocha, Jessica; Rowe, Shawn; Falla, Sigrid
ABSTRACT: This qualitative and exploratory study aimed to understand the experience of adolescents during visits outside the school context in science museums and centres, and how the free-choice learning processes are constructed in this context. We analyzed the visits of four adolescents groups, from public schools, to Maloka (Bogotá, Colombia), and observed the relations of the visitors with their peers, with the exhibits, and with the explainers. For this objective, we examine video and audio recordings in terms of types of interaction and conversational content, seeking to answer: Is the explainer a necessary component of a visit to promote sustained cognitive engagement, or do non-guided activities also create enough interest to promote and sustain cognitive engagement? Active meaning-making was observed during the interactions with exhibits and explainers. In the latter case, the presence of the explainer appears to lead to refinement and complexification were in the sense making and activity of adolescents. In accordance with their sustained engagements and motivations, they mobilized knowledge and previous experiences in the relation with exhibits, in an engaged and autonomous manner, creating learning opportunities based on free-choice, which was reflected in their discussions about scientific themes or in the manual, mental and cultural interactions.